Low-income housing policy : a comparative study of Malaysia and Nigeria / Bawa Chafe Abdullahi - Abdullahi, Bawa Chafe (2013)
Over the decades ago the challenge of the housing policies in the developing countries was to ensure that basic accommodation needs are met and at an affordable price to the majority of the citizens (Harris & Arku, 2007; Tibaijuka, 2009). However, at the same time, housing challenges in developing countries have arisen due to rapid population growth and urbanisation. As a result, governments of these countries face tremendous pressure to provide housing especially decent and affordable for the low-income group (LIG). Meanwhile, there are many especially among the LIG without adequate and affordable housing for now and in the future. Naturally, these dynamics require a policy framework and institutional mechanism that focus on addressing the housing supply to cope with the increasing demand on a sustainable basis. Due to the failure of the prior strategies in the developing countries, beginning in the 1980s, there has been a paradigm shift in low-income housing policies of these countries from state to market driven delivery. As a result, it is being debated on whether neo-liberal housing policy is capable of producing an inclusive and sustainable housing policy outcome. Against this background, a comparative study of low-income housing policy is used to explore how and why there are differences in housing trajectories in Malaysia and Nigeria. The study conceptual framework was based on institutional analysis using structure and agency models within the purview of new institutional economics. As premises of the thesis, these are basic to the understanding of the countries housing policy trajectories in convergence and divergence. Using the case study method, the study results are based on semi-structured and structured questionnaires administered to the public sector policy makers and private sector developers; and LIG households respectively. In addition to, the study data depends on secondary sources. The findings of the study show in spite of the similarities between Malaysia and Nigeria low-income housing policies implemented have produced markedly different and even divergent outcomes, with clear signs of differential impact and experience. Also, the findings indicate that with a more developmentalist state, has more effective implementable low-income housing policy that drives a broader outcome. Similarly, the main findings of this study, not to our surprise, are that national institutional structures and agency responses play an important role in the shaping and determining outcomes of the low-income housing policies. They also highlight the importance of situating housing in a broader institutional context which emphasises the state as an institution matters. These findings establish that the policy success differs according to the state advancing the fundamental institutional legal, fiscal and regulatory frameworks. From the Nigerian context, the case study findings suggest that low-income housing policy strategy has to be state-driven rather than state withdrawal, especially under the neoliberal agenda. On the other hand, from the Malaysian context informed the understanding that this policy requires state political commitment and will concern as the most explicit determinant of success. To this, both contexts emphasises the limitations of the prevailing policy focus on ‗roll-out‘ of state in low-income housing policy. Hence, to reinvent an inclusive housing policy outcome, and avoid the possible consequence this may have for housing delivery by market-led delivery, success presupposes state advancing the interest of its market and society. As a result, the overall ‗vicarious experiences‘ policy learning is that the study context point to the significance of policy autonomy, the institutional framework of implementation, political will and commitment, socio-economic fundamentals and having competent market as a partner. The cross-national comparisons undoubtedly miss the crucial aspects of change over time in LIG housing delivery. Hence, there is a need for longitudinal comparisons and thorough policy research as a basis for sound low-income housing policy.